USING PERSUASIVE COMMUNICATION IN EDUCATION TO PROMOTE BEHAVIOR CHANGE - Kusmawaty Matara; Najamuddin Petta Solong; Syarifuddin; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
In order to improve the quality and effectiveness of the learning process in Indonesia, this research conducts an in-depth study of the application of persuasive communication techniques in education to encourage changes in student behavior. This study uses literature research method. The results show that the use of storytelling and personalized content in the teaching and learning process increases student engagement and helps them understand and remember the material better. In addition, non-verbal aspects of communication, such as eye contact, positive facial expressions, and supportive body gestures, are proven to play a role in increasing the effectiveness of information delivery and strengthening the emotional bond between teachers and students. The implication for education is the need for teacher development and training in persuasive communication techniques as part of professional development. This includes adopting more interactive and responsive learning methods, which not only enrich students' learning experiences but also support the development of 21st century skills such as creativity, problem-solving and cooperation.